Optical Coherence Elastography-Based Corneal Strain Imaging During Low-Amplitude Intraocular Pressure Modulation - Kling, Sabine; Khodadadi, Hossein; Goksel, Orcun (Frontiers in Bioengineering and Biotechnology, 2020)
Purpose: Optical coherence elastography (OCE) is a promising technique for high-resolution strain imaging in ocular tissues. A major strain-inducing factor in the eye is intraocular pressure (IOP), with diurnal physiological fluctuations reaching up to 5 mmHg. We study herein low-amplitude IOP modulation to assess local corneal strain patterns. Methods: Ex vivo porcine eye-globes were adjusted to an initial IOP of 15 and subsequently 25 mmHg. Corneal strain was induced by two subsequent pressure cycles, in which IOP was first increased and then decreased, each by a total of 5 mmHg. 2D-OCT B-scans were recorded after each loading step. Axial strain maps were obtained from magnitude and phase changes, and supra-pixel displacements from cross-correlation. Strain detection sensitivity was evaluated in an isotropic material. Results: Deformations arising from a single 1-mmHg step could be resolved. Largest strain amplitudes (5.11⋅10-3) were observed in the posterior stroma at low initial IOP. Strain amplitude was 1.34 times higher at 15 than at 25 mmHg (p=0.003). Upon IOP increase, anterior cornea was compressed, while posterior cornea showed axial expansion. Both, morphological images and strain maps were sensitive to post-mortem time. Strains larger than 2.44⋅10-5 could be reliably measured. Conclusions: Low amplitude IOP modulation, similar to diurnal physiological changes, induced measurable deformations in corneal tissue. Axial strain maps permit a localized comparison of the corneal biomechanical response. Small strain OCE can likely be extended to other domains.